Information and Communications Technologies Enabling Integrated Primary Care for Patients With Complex Care Needs: Scoping Review - Farah Tahsin; Alana Armas; Apery Kirakalaprathapan; Mudathira Kadu; Jasvinei Sritharan; Carolyn Steele Gray (JMIR Publications, 2023)
BackgroundInformation and communications technologies (ICTs) are recognized as critical enablers of integrated primary care to support patients with multiple chronic conditions. Although ICT-enabled integrated primary care holds promise in supporting patients with complex care needs through team-based and continued care, critical implementation factors regarding what ICTs are available and how they enable this model are yet to be mapped in the literature. ObjectiveThis scoping review addressed the current knowledge gap by answering the following research question: What ICTs are used in delivering integrated primary care to patients with complex care needs? MethodsThe Arksey and O'Malley method enhanced by the work by Levac et al was used to guide this scoping review. In total, 4 electronic medical databases were accessed-MEDLINE, Embase, CINAHL, and PsycINFO-collecting studies published between January 2000 and December 2021. Identified peer-reviewed articles were screened. Relevant studies were charted, collated, and analyzed using the Rainbow Model of Integrated Care and the eHealth Enhanced Chronic Care Model. ResultsA total of 52,216 articles were identified, of which 31 (0.06%) met the review's eligibility criteria. In the current literature, ICTs are used to serve the following functions in the integrated primary care setting: information sharing, self-management support, clinical decision-making, and remote service delivery. Integration efforts are supported by ICTs by promoting teamwork and coordinating clinical services across teams and organizations. Patient, provider, organizational, and technological implementation factors are considered important for ICT-based interventions in the integrated primary care setting. ConclusionsICTs play a critical role in enabling clinical and professional integration in the primary care setting to meet the health system-related needs of patients with complex care needs. Future research is needed to explore how to integrate technologies at an organizational and system level to create a health system that is well prepared to optimize technologies to support patients with complex care needs.